Accuracy of conventional computations in assessing volume of small diameter logs of hopea odorata - Mohd Jamil, A. W.; Faridah, A. A.; Nor Marzuina, F. K. N.; Zafirah, Z. F. (Forest Research Institute Malaysia, 2019)
The accuracy of volumetric computation of small diameter logs based on mathematical formulae was evaluated. Plantation logs of 13-year-old Hopea odorata with diameter measurements of 20 to 30 cm were assessed using Huber’s, Smalian’s, Newton’s and truncated cone formulae. The reference volume of each log was determined using the fundamental method of water-displacement. Results of average values showed that all measurements were higher, compared to reference volume. Empirical evidence indicated that the truncated cone formula was the most precise measurement compared to other formulae. In the analyses of the separated sections, strong linear correlations between mathematical computations and reference volume were observed in middle logs. In contrast, evaluation of bottom and top logs showed lower r2 values. A correction factor was developed and proposed to estimate a more accurate volume of bottom logs. Based on standard geometrical profile of the logs, other plantation species fit for similar computation were suggested.